Remarkable functions of sn-3 hydroxy and phosphocholine groups in 1,2-diacyl-sn-glycerolipids to induce clockwise (+)-helicity around the 1,2-diacyl moiety: Evidence from conformation analysis by 1H NMR spectroscopy - Nishida, Yoshihiro; Yuan, Mengfei; Fukuda, Kazuo; Fujisawa, Kaito; Dohi, Hirofumi; Uzawa, Hirotaka (Beilstein Journal of Organic Chemistry, 2017)
Cell-membrane glycerolipids exhibit a common structural backbone of asymmetric 1,2-diacyl-sn-glycerol bearing polar head groups in the sn-3 position. In this study, the possible effects of sn-3 head groups on the helical conformational property around the 1,2-diacyl moiety in the solution state were examined. 1H NMR Karplus relation studies were carried out using a series of 1,2-dipalmitoyl-sn-glycerols bearing different sn-3 substituents (namely palmitoyl, benzyl, hydrogen, and phosphates). The 1H NMR analysis indicated that the helical property around the 1,2-diacyl moiety is considerably affected by these sn-3 substituents. The sn-3 hydroxy group induced a unique helical property, which was considerably dependent on the solvents used. In CDCl3 solution, three staggered conformers, namely gt(+), gg(−) and tg, were randomized, while in more polar solvents, the gt(+) conformer with (+)-helicity was amplified at the expense of gg(−) and tg conformers. The sn-3 phosphocholine in phosphatidylcholine exhibited a greater effect on the gt(+) conformer, which was independent of the solvents used. From the 1H NMR analysis, the helical conformational properties around the 1,2-diacyl moiety conformed to a simple empirical rule, which permitted the proposal of a conformational diagram for 1,2-dipalmitoyl-sn-glycerols in the solution states.
Keywords: cell membrane; chirality; conformation; deuterium labeling; sn-glycerol; glycerolipids; glycerophospholipids; helicity; Karplus equation; proton NMR spectroscopy; staggered conformers